Extremity soft tissue tumor surgery by surgical specialty: A comparison of case volume among oncology and non‐oncology‐designated surgeons. Issue 3 (3rd July 2013) - Canter, Robert J.; Smith, Caitlin A.; Martinez, Steve R.; Goodnight, James E.; Bold, Richard J.; Wisner, David H.
Abstract Introduction We sought to characterize the extent of extremity soft tissue tumor (ESTT) resections among surgical specialties, hypothesizing that substantial variation exists in the number of ESTT resections performed by specialty. Methods We queried the UHC‐AAMC database for data from 85 institutions for years 2007–2009. We abstracted data on total number of musculoskeletal (MSK) procedures, number of subcutaneous (SQ), deep, and malignant ESTT resections, and anatomic site of resection. Data were available for 4, 682 practitioners including the following specialties: general surgery (GS, N = 2, 195), plastic surgery (PS, N = 792), surgical oncology (SO, N = 533), general orthopedics (GO, N = 1, 079), and orthopedic oncology (OO, N = 83). Results The mean number of all MSK procedures performed per year was 19.0 ± 2.3 GS, 179.6 ± 3.0 PS, 32.4 ± 6.2 SO, 798.6 ± 115.4 GO, and 482.9 ± 6.5 OO (P = 0.001). SQ ESTT resections per year were similar among specialties (1.7 ± 0.3 GS, 2.7 ± 0.3 PS, 2.4 ± 0.4 SO, 1.7 ± 0.5 GO, 4.7 ± 0.2 OO), while deep and malignant resections were more likely performed by OO (combined deep and malignant: 0.9 ± 0.1 GS, 2.0 ± 0.4 PS, 9.9 ± 0.6 SO, 5.8 ± 0.3 GO, and 63.6 ± 8.1 OO, P = 0.001). Adjusting for number of physicians in the database, of the total deep and malignant ESTT resections, 9.4% were performed by GS, 7.7% by PS, 26.0% by SO, 30.8% by GO, and 26.0% by OO. Conclusion Nearly 50% of deep and malignant ESTT resections are performed by non‐oncology‐designated surgeons. Approximately 17% are performed by practitioners who complete an average of one to two of these procedures per year. These findings may have significant implications for quality of care in soft tissue tumor surgery. J. Surg. Oncol. 2013; 108:142–147. © 2013 Wiley Periodicals, Inc.